[Life after the bases ; Sweepstakes draw ; mga kaibigan - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Looks at what may happen after the US military forces pull out of the Philippines, with Sangley Naval Base as a case in point ; the anomaly in the drawing of the first prize winner of Sweepstakes ; and the interview with APO Hiking Society on their 20th year.
Life after the bases (18 min.) -- Sweepstakes draw (17 min.) -- Mga kaibigan (19 min.)
VHS.
Keywords: Apo Hiking Society (Singing group) -- Interviews; Philippine Charity Sweepstakes; Military bases, American -- Philippines; Philippines -- Economic conditions, 1990-.